A Study on the Design of Wayang Babad Kartasura Character Illustrations as a Medium for History Education and Traditional Arts Preservation among Youth in Surakarta - Basnendar Herry Prilosadoso; Agung Purnomo; Ana Rosmiati; Indriati Suci Pravitasari; Indriana Anggun Febrianti; Putri Sekar Hapsari; Hening Laksani; Sri Murwanti; Daffaa Gisti Aaqilah; Muhammad Bagus Kafabik; Ditya Fajar Rizkizha (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
The declining interest of younger generations in local history and traditional arts has created significant challenges for the preservation of Wayang Babad Kartasura in Surakarta. This study aims to examine the design characteristics of Wayang Babad Kartasura illustrations, explore their educational values, and analyze their potential as a medium for history education and cultural preservation among youth. Employing a qualitative descriptive approach with a case study design, the research was conducted in Surakarta between January and June 2026. Data were collected through semi-structured interviews, observations, and document analysis involving puppeteers, cultural practitioners, historians, teachers, and students selected through purposive sampling. The findings reveal that Wayang Babad Kartasura possesses distinctive visual features that differentiate it from conventional Wayang Purwa, particularly through the realistic representation of historical figures and narratives surrounding the political transition from Kartasura to Surakarta. The performances embody educational values related to leadership, morality, social responsibility, and cultural identity. However, challenges such as linguistic barriers, limited regeneration, and inadequate promotion continue to hinder its sustainability. The study further demonstrates that the development of character illustrations, supported by digital media and cross-sector collaboration, offers an effective strategy for increasing youth engagement with local history and traditional arts. This research contributes to the growing discourse on cultural preservation by highlighting the role of visual adaptation in transforming historical heritage into educational resources relevant to contemporary society.